Reasons for Temporary or Permanent Suspension of Using Electronic Accounts on Social Media Platforms - Kamel, Ahmed Mostafa (Dirasat: Human and Social Sciences, 2023)
Objectives: The study aims to achieve a better understanding of the reasons for the temporary or permanent suspension of using the electronic account on a platform or more of social media among Egyptian youth. Methods: This research is a descriptive research ; the researcher depends on a questionnaire to collect data that was applied to a sample of Egyptian youth between the age of 18 to 35 years old (225 individuals). They represent 3 different regions which are (Cairo,Giza, and Assuit). Results: The research has reached many results, including the decision to temporarily or permanently suspension using a social media platform was not a difficult decision it was previously taken by 86.7% of youth from the sample of the study. The study also found the most important reasons for the temporary or permanent suspension from using the electronic account, including social problems, privacy, disconnection from others, or the desire to escape from threats or prosecutions, etc. Conclusions: The study concluded the importance of providing enough awareness and protection for young people that use social media platforms, and preparing future comparative studies between various societies that explain the different reasons for stopping the use of these platforms.